The SAGE handbook of applied social research methods - Bickman, Leornard , 1941-; Rog, Debra J. (SAGE Publications, 2009)
"Provides students and researchers with a comprehensive resource that covers core methods, research designs and data collection, management, and analysis issues. The only handbook to focus on the multimethod and interdisciplinary application of social research, it covers both qualitative and quantitative approaches and places critical emphasis on finding the tools that best fit the research question given the constraints of deadlines, budget, and available resources"--Jacket.